Treatment Effects of the Herbst Appliance in Class II Malocclusion Patients after the Growth Peak - Cançado, Rodrigo Hermont; Janson, Guilherme; Tompson, Bryan; Alvares, José Carlos de Castro; Valarelli, Fabrício Pinelli; Freitas, Karina Maria Salvatore (European Journal of Dentistry, 2020)
Objective The aim of this study was to evaluate dentoskeletal changes in the treatment of Class II malocclusion with the Herbst Cantilever Bite Jumper (CBJ) appliance, associated with multibracket appliances after the growth peak, at pretreatment.Materials and Methods  A sample of 37 individuals was divided into two groups: the experimental group comprised 16 patients treated consecutively for a mean period of 2.52 years with the Herbst CBJ appliance associated with multibracket appliances. A total of 21 subjects (10 males and 11 females) with Class II malocclusion and mean age at T1 of 16.08 years were followed for a mean period of 2.12 years composed the control group. Comparisons between the two groups were performed using initial and final lateral cephalograms. Comparisons between experimental and control groups at pretreatment and of the treatment changes were performed by Mann–Whitney or independent t-tests.Results Experimental group exhibited a significantly greater labial inclination of the mandibular incisors in comparison to the control group. Additionally, significantly greater corrections in overbite, overjet, and molar relationship were observed in the experimental than in the control groups.Conclusion The effects of the Herbst CBJ appliance, associated with fixed appliances after the growth peak in Class II malocclusion treatment are correction in molar relationship toward a Class I relationship, decrease of the overjet, decrease of the overbite, and mandibular incisors labial inclination.
Keywords: angle Class II malocclusion; young adult; cephalometry; age factors